Orientación Vocacional y Rendimiento Académico de los estudiantes del I ciclo de la facultad de Educación y Humanidades - Rioja de la Universidad Nacional de San Martín en el semestre académico 2008- I - Lozano Paz, María Elvia (2009)
The increasing importance that the science has acquired in our society and the paper(role) increasingly relevant that the scientist recovers(plays) in the human occupation, to salve the problems in a society, is a need of the universities to form(train) investigators(researchers) in each of the areas of the science. The investigators'(researcher) formation (training) is directly linked by the education. In the Faculty (Power) of Education Humanities, located in the province of Rioja, of the National University of St Martin, have the opportunity to develop in the study plan of the professional career (race), subjects orientated to the orientation vocational they are: Methodology of the orientation vocational in students del I cycle en semester academic 2000-I de la Faulted de Education, y Humanities-Rioja de la Universidad National de San Martín-Tarapoto. The curriculum of the Faculty (Power) of Education and Humanities it (he) is orientated to that his (her, your) gone away ones (graduated ones) are capable of realizing scientific investigation (research). lt is important to indicate that a separation exists between (among) the systematizing of the experiences of learning and the results that are waited, on to having executed the above mentioned experiences of learning. Therefore, it is necessary to realize an investigation (research) that is orientated to relate the attitudes towards the orientation vocational and the academic performance (yield). From the perspective, the aim(lens) of the investigation(research) is to determine the relation that exists between(among) the attitudes towards the orientation vocational and the academic performance(yield) of the students del I cycle in the academic semester 2008-I, of the Faculty(Power) of Education and Humanities-Rioja of San's Martin National University-Tarapoto; hipotetizando that the attitudes towards the orientation vocational relates directly proportionally to the academic performance(yield) of the students del 1 cycle in the academic semester 2008-I, of the Faculty(Power) of Education and Humanities-Rioja of San's Martin National University-Tarapoto. The sample was constituted by 18 students belonging to the I cycle of the professional careers (races) of the initial level, primary and secondary, in the academic semester 2008-1. Gathered the information of this sample and accused by means of her (it) t - student, where tc:-2, 87 it (he, she) falls down in the region of rejection, being ft:-2, 101. Since (as, like) te Ɛ RR, has allowed to reject the void hypothesis and to accept the alternate one, in consequence, is confirmed that the attitudes towards the orientation vocational it (he, she) relates directly proportionally to the academic performance (yiela) of the students 1 cycle in the academic semester 2008-1, of the Faculty (Power) of Education and Humanities-Rioja of San's Martin National University-Tarapoto.